First principles study of Ti-Zr-Ta alloy phase stability and elastic properties. (1st February 2023) - Ruobing, Zhang; Lin, Ai
Abstract: The effects of Ta and Zr content on the stability, elastic properties and electronic structure of Ti-Zr-Ta alloy phase were studied by first principles calculation method based on density functional theory. Moreover, Ti-Zr-Ta alloy was fabricated by spark plasma sintering (SPS) using spherical Ti powder, Ta powder, and Ti-Zr-Ta alloy powder produced by the plasma rotation electrode process (PREP). Afterward, the effects of sintering temperature, Zr and Ta content on the microstructure and mechanical properties of the alloy samples were investigated. The results showed that sintering temperature, Ta and Zr content were the key factors which affected the densification. When the sintering temperature was raised, the relative density and mechanical properties of Ti-Zr-Ta alloy were significantly increased. The first- principles calculation also indicated that Ti-1Zr-Ta possesses the lowest Young's modulus and the best ductility, showing great potential of biomedical applications which agrees with the results of experimental results of alloy preparation.